2019
DOI: 10.1111/sms.13373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral curcumin ingested before or after eccentric exercise on markers of muscle damage and inflammation

Abstract: We examined the effect of curcumin (CUR) ingestion before or after exercise on changes in muscle damage and inflammatory responses after exercise. We conducted two parallel experiments with different CUR ingestion timings using a double‐blind crossover. In Exp. 1, ten healthy men ingested 180 mg d−1 of CUR or placebo (PLA) 7 days before exercise. In Exp. 2, ten other healthy men ingested 180 mg d−1 of CUR or PLA 7 days after exercise. They performed 30 maximal isokinetic (120°s−1) eccentric contractions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(155 citation statements)
references
References 42 publications
4
131
1
1
Order By: Relevance
“…Previous research has indicated that curcumin may have antioxidant, anti-inflammatory, and analgesic effects on DOMS [24]. Furthermore, similar effects of curcumin have been described by Tanabe et al [1], who found that ingestion before exercise could attenuate acute inflammation, and after exercise, it could attenuate muscle damage and facilitate faster recovery. Drobnic et al [5] reported a reduction in muscular trauma with a moderate reduction in pain with curcumin supplementation.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Previous research has indicated that curcumin may have antioxidant, anti-inflammatory, and analgesic effects on DOMS [24]. Furthermore, similar effects of curcumin have been described by Tanabe et al [1], who found that ingestion before exercise could attenuate acute inflammation, and after exercise, it could attenuate muscle damage and facilitate faster recovery. Drobnic et al [5] reported a reduction in muscular trauma with a moderate reduction in pain with curcumin supplementation.…”
Section: Introductionsupporting
confidence: 63%
“…In addition, Delecroix et al [31] chose a combination of curcumin plus piperine in the composition. Regarding the daily dose of curcumin, seven studies used doses ranging from 150 to 1500 mg [1,2,4,5,10,24,25,30,32], and two studies tested higher doses of about 5 g [28] and 6 g [31] daily. In nine of the included studies, supplementation was given before and after exercise [1,2,5,10,25,28,[30][31][32], Sciberras et al [4] used curcumin before exercise, and Nakhostin-Roohi et al [24] supplemented with curcumin after exercise.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Its mechanism of action is supposed to involve membranes crossing and the stabilization of the excitation-contraction coupling in myocytes, preserving the contractile function, especially of Type II fibers, which are the ones maily involved in eccentric contractions. Another study by Tanabe et al [15] supports the use of a nutraceutical compound, curcumin, in order to overcome the possible side effects of high-intensity eccentric exercise and faster recovery in case of muscle damage. Curcumin supplementation, after exercise, was shown to improve muscle strength, range of motion, pain, and serum creatine kinase activity, while curcumin supplementation before exercise attenuated the early inflammatory makers (IL-8).…”
Section: Highlight By Silvia Ravallimentioning
confidence: 98%